Study on Limitations and Challenges of Walkability Research: Exploring the Walkability Challenges in Indian Urban Communities (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Reason Indian urban communities have consistently been urban areas of walkers. The reason for this research is to endeavor to inspect the walkability of City of Hyderabad and frameworks the issues, challenges and degree for working on its walkability. A review of 100 individuals having a place with the working class and lower working class was led through an organized poll relating to the person on foot hardships and arrangements. The specialist alongside a gathering of understudies then, at that point really strolled every one of the courses and gathered more explicit data. Discoveries It is seen that Indian urban areas are turning out to be progressively dangerous for people on foot. Walkways and asphalts simply don't exist. On the off chance that an asphalt exists it is ineffectively developed and severely kept up with. An endeavor was made to determine a walkability rating for the city of Hyderabad. Down to earth suggestions This study features a few strategy proposals for improving the current passerby framework and gives walker centered arrangements.